Complications and long-term outcomes after endovascular treatment of basilar trunk aneurysms - Bi, Yuange; Tian, Yangyang; Chi, Yunbo; Chen, Xiaohan; Song, Xiaopeng; Chen, Xuan; Yang, Zhongxi; Zhou, Jing (Frontiers in Neurology, 2025)
PurposeBasilar trunk aneurysms (BTAs) are rare and challenging to treat, with a high complication rate. This study aimed to analyze and evaluate the complications and long-term outcomes associated with endovascular treatment (EVT) of BTAs and identify risk factors for post-procedural complications and unfavorable clinical outcomes.MethodsThis retrospective, observational cohort study included 90 patients (92 BTAs) treated with EVTs from January 2011 to April 2023. Factors associated with post-procedural complications and unfavorable clinical outcomes were analyzed.ResultsAll 90 patients (92 aneurysms) were successfully treated, of which 63 (68.5%) aneurysms were small, 26 (28.3%) were large, and 3 (3.3%) were giant; 23 (25%) were saccular, and 69 (75%) were fusiform and/or dissecting. A total of 36 (40.0%) patients were admitted with ruptured aneurysm. The median follow-up duration was 51.0 months (IQR 21.0–3.0). The favorable clinical outcome rate was 75.6% (68/90). The overall complication rate was 33.33% (30/90), with ischemic and hemorrhagic complications occurring in 25.6% (23/90) and 2.2% (2/90) of cases, respectively. The mortality rate was 8.9% (8/90). Unilateral vertebral artery sacrifice (P = 0.015), Glasgow Coma Scale (GCS) grade ≤12 before the procedure (P < 0.047), and age ≥60 years (P = 0.006) were associated with overall post-procedural complications. Diabetes mellitus (P = 0.002), ischemic onset (P = 0.005), aneurysms involving the vertebrobasilar junction (P = 0.025), and GCS grade ≤12 before the procedure (P < 0.001) were risk factors for unfavorable clinical outcomes. Cumulative survival rates at 1, 3, and 5 years were 95.4%, 92.1%, and 87.9%, respectively. The cumulative complication-free survival rates were 72.1%, 68.3%, and 64.5%, respectively. Angiographic follow-up revealed complete occlusion in 71.7% (33/46).ConclusionEVT for BTAs appears feasible and yields favorable clinical outcomes at the last follow-up, with reasonable cumulative survival rates at 1, 3, and 5 years. However, clinicians should be vigilant for procedure-related complications, particularly ischemic complications, which may lead to poor outcomes or death.